Multi-energy microgrid optimal operation - Chen, Yumin (Nanyang Technological University, 2020)
With the increasing demand for global energy, multi-energy microgrids have drawn more attention in recent years. In a multi-energy microgrid (MEMG), different kinds of energies like heat, electricity, cooling, and gas are interacted with each at various levels, aiming to increase the overall energy utilization efficiency. MEMG usually contains many different generation units and ancillary components like combined heat and power (CHP) plant, photovoltaic cell (PV), wind turbine (WT), electric boiler (EB), fuel cell (FC), energy storage (ES) and so on. Since the operational properties and technical limits are quite different, how to optimally dispatch these units is a key research topic in this area. Besides, the properties of these energy networks are also different. For instance, we usually assume that electricity can be delivered to customers immediately without any time delay. However, in the heat network, thermal energy is transferred by hot water in pipes. Since the flow rate of hot water is much slower than the transmission speed of electricity, there is a transmission delay ranging from minutes to hours in the heat network. Thus, it is valuable to consider the transferring time delay in MEMG. What’s more, the uncertainties of renewable energy resources pose a significant challenge to the operation of MEMG. The focus of this research topic is to propose a suitable coordinated operation method for MEMG with coupled heat and electrical networks, in which the specific models of electrical network and heat network are systematically studied. Further, demand response management (DRM) and the randomness of renewable energy resources are considered in the proposed method to better operate MEMG. All the proposed operation and planning methods have been verified in simulation using GAMS and HOMER. The proposed method is simulated on a MEMG with coupled heat and electrical network, which is based on the IEEE 33-bus radial distribution network and a 13-pipe DHN.